2015
DOI: 10.1515/bjdm-2015-0031
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and associated socio-demographic factors in adult people in Bulgaria

Abstract: SUMMARYObjective: The study aimed to establish the mean DMFT of adults over the age of 20 years in Bulgaria. We also aimed to determine any association between demographic factors, such as age, gender, general health status etc, and dental caries.Material and Methods: The study was conducted from 2006 to 2009. Data was collected from a randomly chosen representative sample of 1741 adults aged over 20 years, from 13 Bulgarian cities and villages. From these 1741 adults, 105 (6.03%) refused to complete the quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
(11 reference statements)
2
1
1
1
Order By: Relevance
“…ues can vary significantly depending on age, gender and general health (45). Bego et al have found the difference in the incidence of dental caries in adults and higher DMF index values in women than in men, which corresponds to the current data in Croatia (18).…”
Section: Sukob Interesasupporting
confidence: 71%
See 1 more Smart Citation
“…ues can vary significantly depending on age, gender and general health (45). Bego et al have found the difference in the incidence of dental caries in adults and higher DMF index values in women than in men, which corresponds to the current data in Croatia (18).…”
Section: Sukob Interesasupporting
confidence: 71%
“…Poznato je da mnogobrojni socijalno-ekonomski i demografski čimbenici, kao što su dob, spol, urbanizacija, ekonomski uvjeti i drugo, utječu na oralni status i prevalenciju karijesa (43,44). Bonev i ostali objavili su podatke o KEP-u odrasle populacije u Bugarskoj (17,7) koji govore u prilog tome da vrijednosti KEP-a mogu značajno varirati u odnosu na dob, spol i opće zdravstveno stanje (45). Bego i ostali došli su do razlike u pojavnosti karijesa kod odraslih te su ustanovili veći European countries have a lower relative risk (RR) compared with the European region's average, while 24 European countries have a rate of decay higher than the average for the region.…”
Section: Radić I Surunclassified
“…A weak correlation between dental fluorosis and dental caries (r = .035) was reported in our study, which was contradictory to the findings by Grobleri SR et al 20 , Woondwossen F et al 32 , whereas similar findings to our studies have been reported as well by other studies 33 . In the current study, a statistically significant association was observed between gender and carious lesions, similar to other studies 34,35 . However, no there was significant association between gender and fluorosis, contrary to other studies 36 which could be attributed to the varying levels of fluoride in water and is a geographical factor.…”
Section: Resultssupporting
confidence: 92%
“…In our study, we found higher values of dental caries distribution, and, the coeffi cient of DMFT (12.55 ± 5.545) compared to the data obtained from other geographical regions. Higher values of DMFT index for our country have been reported by Bonev B. et al: 17.8 ± 7.98 [26]. These diff erences are probably related not only to the size of the sample used but also to the place of living of the studied groups.…”
Section: Discussioncontrasting
confidence: 46%